Pendapatan Usahatani Kelapa Di Desa Agotey Kecamatan Mandolang Kabupaten Minahasa - Deri Anggreini Br. Sitepu Sitepu; Grace A. J. Rumagit; Tommy F. Lolowang (Sam Ratulangi University, 2022)
This research aims to analyze the level of income of coconut farming in Agotey Village, Mandolang District. The research was carried out for 2 months, from August to October 2021 in Agotey Village, Mandolang District, Minahasa Regency. The data used are primary data obtained through direct interviews with coconut farmers using a questionnaire. Secondary data was obtained through the Agotey Village Office and the Minahasa Central Statistics Agency. Sampling was carried out using the Accidental Sampling method, namely as many as 20 land-owning farmers who have been running coconut farming for a long time. The results of this study indicate that the average income per hectare of coconut farming in Agotey Village, Mandolang District, Minahasa Regency for one year is Rp. 6,591,213 obtained from the difference between the average revenue of Rp. 16,701,850 minus the cost of Rp. 10,110,637.